EXPRESSIVE SPEECH ACTS IN 'LAKON POLITIK REPUBLIK' EPISODE OF 'MATA NAJWA' TALKSHOW - Fajar Indah Nuraini; Dwi Santoso; Novi Sri Rahmi; Rosa Oktavia Kaptania (Leksema: Jurnal Bahasa dan Sastra, 2020)
The objectives of this research are to find out the types of expressive speech act and the forms of expressive speech act in Mata NajwaTalkshow: Lakon Politik Republik Episode. It is interesting to analyze expressive speech since all the human beings are given a feeling by God and they tend to express their psychological feeling. Feeling is strictly related to expressive speech act. Kreidler and Frank’s theory about expressive speech act was used in this research .This research belongs to qualitative. Furthermore, the data of this research are the utterances containing expressive speech act in Mata Najwa Talkshow: Lakon Politik Republik Episode. In collecting the data, the researchers decide to use documentation technique. The four researchers analyze the data by identifyingand classifying the data into types and forms of expressive speech act. The results are 13 types of expressive speech act and 2 forms of expressive speech act are found in this research. The types are thanking, regretting, apologizing, praising, liking, disliking, approving, disapproving, condoling, criticizing, boasting, lamenting, blaming. The forms of expressive speech act found by the researchers are declarative and interrogative.